The Leadership Strategies of Accredited A Elementary School Principals in Improving Education Quality - Puspita, Nimas Bella; Sumarsono, Raden Bambang; Sunarni, Sunarni; Arifin, Imron (Proceedings Series of Educational Studies, 2024)
This study aims to determine: 1) the leadership strategy steps of A-accredited elementary school principals in improving the quality of education; 2) the leadership competencies of A-accredited elementary school principals in enhancing the quality of education; and 3) the indicators of quality improvement through the leadership strategies of A-accredited elementary school principals. This research employs a qualitative approach with a multi-site method located at SDN 1 Balong and SDN 3 Bangunsari Ponorogo. Data collection techniques include interviews, observations, and documentation studies. The results show that: 1) the leadership strategy steps of A-accredited elementary school principals in quality improvement include: formulating a clear vision, improving Education Report Card scores, maintaining the quality of learning, building good coordination with school stakeholders, and maintaining the school's image; 2) the leadership competencies encompass personality, managerial, entrepreneurial, supervisory, and social competencies; and 3) the indicators of quality improvement through the leadership strategies of A-accredited elementary school principals are fulfilled by meeting the eight of National Education Standards. Keywords: school leadership; accreditation; education quality